La vie sexuelle des anthropologues : subjectivité érotique et travail ethnographique - Don Kulick (Genre, Sexualité et Société)
This text is an introduction to Taboo, Sex, Identity and Erotic Subjectivity in Anthropological Fieldwork (1995), by Don Kulick and Margaret Willson, a collection of articles considering the fieldworker erotic subjectivity as a useful medium to understand central anthropological questions. Here Kulick is trying to acknowledge and question a sexual and erotic reflexivity. He proposes to think the anthropological interest in the sexuality of the studied people, the growing movement of reflexivity in anthropology and the astonishing silence surrounding the anthropologist as a sexual subject. He discusses what should be the meaning of words like sex and sexuality, and especially how they are employed by the fieldworkers who reached he’s request for testimonies and articles.